Dabigatran - a continuing exemplar case history demonstrating the need for comprehensive models to optimize the utilization of new drugs - Godman, Brian; Malmström, Rickard E.; Diogene, Eduardo; Jayathissa, Sisira; McTaggart, Stuart; Cars, Thomas; Alvarez-Madrazo, Samantha; Baumgärtel, Christoph; Brzezinska, Anna; Bucsics, Anna; Campbell, Stephen; Eriksson, Irene; et al. (Frontiers in Pharmacology, 2014)
Background: There are potential conflicts between authorities and companies to fund new premium priced drugs especially where there are effectiveness, safety and/ or budget concerns. Dabigatran, a new oral anticoagulant for the prevention of stroke in patients with non-valvular atrial fibrillation (AF), exemplifies this issue. Whilst new effective treatments are needed, there are issues in the elderly with dabigatran due to variable drug concentrations, no known antidote and dependence on renal elimination. Published studies showed dabigatran to be cost-effective but there are budget concerns given the prevalence of AF. These concerns resulted in extensive activities pre- to post-launch to manage its introduction. Objective: To (i) review authority activities across countries, (ii) use the findings to develop new models to better manage the entry of new drugs, and (iii) review the implications based on post-launch activities. Methodology: (i) Descriptive review and appraisal of activities regarding dabigatran, (ii) development of guidance for key stakeholder groups through an iterative process, (iii) refining guidance following post launch studies. Results: Plethora of activities to manage dabigatran including extensive pre-launch activities, risk sharing arrangements, prescribing restrictions and monitoring of prescribing post launch. Reimbursement has been denied in some countries due to concerns with its budget impact and/or excessive bleeding. Development of a new model and future guidance is proposed to better manage the entry of new drugs, centring on three pillars of pre-, peri- and post-launch activities. Post-launch activities include increasing use of patient registries to monitor the safety and effectiveness of new drugs in clinical practice. Conclusion: Models for introducing new drugs are essential to optimise their prescribing especially where concerns. Without such models, new drugs may be withdrawn prematurely and/ or struggle for funding.